Analisis Faktor-Faktor Yang Mempengaruhi Konsumsi Beras di Provinsi Bali - Putra, I Putu Danendra; Wardana, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.06.TAHUN 2018DO - 10.24843/EEB.2018.v07.i06.p04, 2018)
Rice is a basic and primary requirement of Balinese people as the main source of carbohydrates. Consumption rice in Bali Province continues to increase every year but not offset by increased rice production. This study aims to determine how the influence of rice prices, the number of residents, the number of visits of domestic tourists and the number of foreign tourists visiting the consumption of rice and bagimana Gross Regional Domestic Product (PDRB) moderate the influence of rice prices and the population of rice consumption. Sources of data used in this study are secondary data obtained from the Central Bureau of Statistics Bali Province, Bali Provincial Agriculture Office, Bali Provincial Tourism Office and other related offices. The analysis used in this research is descriptive analysis and associative analysis using multiple linear regeresis analysis, moderating variable analysis. The result of analysis shows the number of population, the number of domestic tourist visit and the number of foreign tourist visit have positive and significant influence to the consumption of rice, while the price of rice have negative but insignificant effect to the consumption of Bali Provincial rice in 1983-2016. GRDP significantly strengthens the influence of rice prices and population on rice consumption of Bali Province in 1983-2016.